International Evidenceon the Determinants of Trade Dynamics - Prasad, Eswar (IMF Working Papers; Working Paper ;, 1997)
This paper provides some new empirical perspectives on the relationship between international trade and macroeconomic fluctuations in industrial economies. First, a comprehensive set of stylized facts concerning fluctuations in trade variables and their determinants are presented. A measure of the quantitative importance of international trade for the propagation of domestic business cycles is then constructed, focusing on the role of external trade as a catalyst for cyclical recoveries. Finally, structural vector autoregression models are used to characterize the joint dynamics of output, exchange rates, and trade variables in response to different types of macroeconomic shocks.